Oyconyms of West and Middle Polissia ending in *-ьn: areal and chronological aspects (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article is devoted to areal and chronological aspects of learning of oyconyms of West and Middle Polissia ending in *-ьn. Spatial and temporal characteristic of geographic names is a part of their stratigraphy. Stratigraphic method is used in complex formant studies of Slavonic oyconymy, because it provides localization of geographic names, finding out the chronology of toponyms and its quantitative characteristics. Areal studies of geographic names of this type in diachrony allow considering deeply oyconymic space, to characterize it, to determine its peculiarities in different historical periods and this leads to conclusions about the dynamics of onyms. Chronological aspect of studying of oyconymic types is to fix each onym from the first mention in historical documents to nowadays. It is accented that oyconyms ending in *-ьn are genetically connected with relative adjectives and it is fixed a great part of geographic names with this suffix after the process of substantivation in Ukrainian oyconymy. Word-forming basis of these oyconyms are appellative relative adjectives ending in *-ьn which constantly form new onyms nowadays (in present days – microtoponyms). Relative adjectives are tightly connected with nouns; they evidently were one of the most archaic types and are not so widely represented in Ukrainian oyconymy because time partly removed them from the map. However cycle is inherent in “fashion”. And that is why oyconyms with the suffix *-ьn intensified again in XIХ–XХI centuries. A lot of secondary names which were created indirectly arise in that period. Among oyconymic archaisms there are few names ending in *-ьn; they are mainly creations of the newest epoch in Ukrainian history. Toponyms ending in *-ьn are fixed on All-Slavonic territory and they are “viable” in toponymy nowadays. Mechanism of formation of oyconymy ending in *-ьn at the initial stage and in last centuries differs much: the first ones had a direct connection with a nature of geographic object; the second ones were formed according to appropriated formal scheme. West and Middle Polissia is the region of Ukraine which is interesting for onomasts because this territory represents a significant massif of archaic oyconyms, and geographic names ending in *-ьn in particular. These onyms are part of All-Ukrainian and All-Slavonic areas.
Keywords: stratigraphy; area; chronology; archaic oyconym; oyconym ending in *-ьn